PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI - Martini; Masganti Sitorus (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI STAI DINIYAH PEKANBARU, 2023)
With the addition of more complicated physical structures and functions in speech and language, basic and fine motor abilities, socialization, and independence, development is a shift that lasts a lifetime. The process of thinking that includes the capacity to relate, evaluate, and take into account an event or events is known as cognitive development. Although cognitive capacity is predetermined at conception (fertilization), how it develops relies on the surrounding circumstances and chances. The research methodology employed in this study combined document-based data collecting with library research. After gathering the data, the researcher analyzed it by reading, examining, and drawing conclusions from it. The objectives of this study were to determine early childhood cognitive development and expert theories on cognitive development. The application of the evaluation of kids’s cognitive improvement is important to perform that allows you to realize the fulfillment of kids’s cognitive improvement greater efficaciously, in step with the findings of numerous studies. According to research, kindergarten evaluations can be used to determine how early childhood cognitive development is progressing.english version, written using Time New Roman-11, italic. Abstract contain research aim/purpose, method, and reseach results; written in 1 paragraph, single space among rows, using past tense sentences.